Wild Pedagogies: Six Initial Touchstones for Early Childhood Environmental Educators - Jickling, Bob; Blenkinsop, Sean; Morse, Marcus; Jensen, Aage (Australian Journal of Environmental Education, 2018)
This article is a small piece of a much larger and still evolving project. Herein we focus on six touchstones for wild pedagogies. The article begins with a short orientation to the larger ideas behind the project and then focuses on exploring six current touchstones with a view towards early childhood environmental educators. The six explored here are: (1) agency and the role of nature as co-teacher; (2) wildness and challenging ideas of control; (3) complexity, the unknown, and spontaneity; (4) locating the wild; (5) time and practice; and (6) cultural change.
Publisher: Cambridge University Press
Keywords: agency; change; control; environment; environmental education; pedagogies; practice; time; wild; wildness